Simulation and Implementation of Interleaved Boost DC-DC Converter for Fuel Cell Application - Ahmad Saudi Samosir; NFN Taufiq; Abdul Halim Mohd Yatim (Institute of Advanced Engineering and Science, 2011)
This paper deals with a boost dc-dc converter for fuel cell application. In fuel cell electric vehicles application, a high power boost dc-dc converter is adopted to adjust the output voltage, current and power of fuel cell engine to meet the vehicle requirements. One of challenge in designing a boost converter for high power application is how to handle the high current at the input side. In this paper an interleaved boost dc-dc converter is proposed for current sharing on high power application. Moreover, this converter also reduces the fuel ripple current. Performance of the interleaved boost converter is tested through simulation and experimental results.Keywords: component; Interleaved Boost Converter; Fuel Cell Electric Vehicle; high power application.DOI: http://dx.doi.org/10.11591/ijpeds.v1i2.126